Prawo do nauki (art. 2 Protokołu nr 1 do Konwencji) a numerus clausus w szkolnictwie wyższym – uwagi na tle wyroku Europejskiego Trybunału Praw Człowieka z 2 kwietnia 2013 r. w sprawie Tarantino i inni przeciwko Włochom - Jakubowski, Aleksander (Wydawnictwo Naukowe UAM, 2014)
The right to education which is guaranteed in Article 2 of Protocol No. 1 to the European Convention of Human Rights and Fundamental Freedoms is deemed to be fundamental, and provides grounds for formulating the rights of an individual and, corresponding to them, duties of a public government. The right to education includes 3 elements: the right to access the existing institutions and learning programs, the right to receive real and effective education, and the right to have the education completed within the existing recognised educational systems. These three rights also refer to higher education, including the private one, at all levels: bachelor studies, master studies and doctoral studies. As can be noticed in the ECHR decisions, access to education can never be limited on the grounds that are illegal, arbitral, irrational or simply discriminatory. This access must be framed and realised in a manner respecting the principle of equality, which follows from the conviction that everyone is entitled to have not only access to education but also to have this access provided on the same terms as it is provided to all individuals in an analogical situation. The similarity in this context is measured i.a. by comparing the levels of candidates’ capabilities and qualifi cations, which constitute a justifi ed and objective set of criteria. These directives were taken into consideration in the judgment of the ECHR of 2 of April 2013 in the case of Tarantino and others v. Italy. The Tribunal has ruled that the Italian regulation introducing the limit of admissions (numerus clausus) in higher education is in accordance with the right to education stated in the Convention. It was recognised that making the admission to the higher education conditional on the intellectual capabilities of a candidate is justifi ed and consistent with the essence of the right to education. The Tribunal’s ruling has a substantial importance for Polish regulations which are similar to those in the analysed case under consideration. The remarks made by the ECHR exceed the issue of numerous clauses and address the whole substance of the right to education, including the right to gain benefi ts of education or the influence of the conditions of the access to education on the nature of the right stated in the Article 2.
The right to education (Article 2 of Protocol No. 1 to the Convention) and numerus clausus in higher education – some remarks on the background of the judgment of the European Court of Human Rights of 2 April 2013 in the case of Tarantino and others v. Italy
Keywords: the right to education; the higher education; education; numerus clausus